NT-proBNP levels and mortality in a general population-based cohort from Turkey: a long-term follow-up study. (7th September 2018) - Simsek, Mustafa Aytek; Degertekin, Muzaffer; Turer Cabbar, Ayca; Aslanger, Emre; Ozveren, Olcay; Aydın, Sinan; Mutlu, Bulent; Erol, Cetin
Aim: We investigated the relationship between NT-ProBNP and mortality in a general population-based cohort.Methods & Results: A total of 2021 out of 4650 participants from previously published HAPPY study were included. Mean follow-up was 84.5 ± 10.4 months. After adjusting for risk factors, high levels of LogNT-proBNP predicted all-cause death (HR: 3.23; 95% CI: 2.20–4.75; p < 0.001) and cardiovascular death (HR: 3.85; 95% CI: 2.37–6.26; p < 0.001). Regression analysis revealed that LogNT-proBNP was an independent predictor of all-cause death (HR: 2.85; 95% CI: 1.91–4.24; p < 0.001) and cardiovascular death (HR: 3.02; 95% CI: 1.84–4.95; p < 0.001).Conclusıon: Our study showed that in long term follow-up, NT-proBNP is associated with increased all-cause and cardiovascular mortality